Histopathological and ultrastructural changes experimentally induced by bee venom in seminiferous epithelium via structural-functional alteration of Sertoli cells. (November 2017) - Florea, Adrian; Puică, Constantin; Hamed, Sami; Tilinca, Mariana; Matei, Horea
Highlights: Exposure of rats to bee venom subchronic low doses, and acute semilethal dose. Better observation of histopathological aspects with the new staining method. Extensive unspecific ultrastructural alterations of Sertoli cells. Reduced thickness of spermatogenic epithelium in both experimental conditions. Reduced Sertoli cells count in both experimental conditions. Abstract: We tested here the ability of bee venom (BV) to interfere with spermatogenesis in rats in two experimental conditions. The histopathological changes were assessed with brightfield microscopy using a novel staining technique, based on methylene blue, orange G and ponceau xylidine. Transmission electron microscopy was also used to identify fine subcellular changes. BV injection for 30 days in daily doses of 700 μg BV/kg resulted in reducing testicular weight, along with significant larger diameters of seminiferous tubules and reduced number of Sertoli cells (SCs). SCs were vacuolated, detached from the basement membrane, many necrosed, leading to the basement membrane denudation. Germ cells layers were separated by empty spaces conferring a rarefied aspect to the tissue, and spermatids were detached into lumen. Thus, the seminiferous epithelium was significantly thinned. Many Leydig cells (LCs) were in a necrotic state, with disrupted plasma membrane and without smooth endoplasmic reticulum. The acute treatment with a single LD50 of 62 mg BV/kg, was followed by focal disruptions of the basement membrane and localized areas of necrosis, mainly affecting the SCs. Most of the observed SCs as well as some spermatogonia were highly vacuoled, empty spaces being observed within the epithelium. The SCs count was significantly decreased. Spermatids had also the tendency of separation from the SCs, and the significant larger diameter of the tubules found was associated with a thicker epithelium. Many LCs were necrosed, with disrupted plasma membrane, swollen mitochondria, no endoplasmic reticulum and implicitly showing rarefied cytoplasm. We concluded that BV was a testicular toxicant affecting both the LCs and the seminiferous tubules. The SCs cells represented the primary target site of BV whose effects were next extended upon the germ cells. In all cells, BV triggered unspecific degenerative changes that could impaire spermatogenesis. The present study also proposes an alternative staining technique very useful in assessing the histopathological aspects of spermatogenesis.